TJS 2016
DOI: 10.15547/tjs.2016.01.013
|View full text |Cite
|
Sign up to set email alerts
|

Morphological and phenotypic characteristics of donkeys in some regions of Bulgaria

Abstract: The aim of the recent study was to determine the morphological characteristics of the donkey population in some areas of Bulgaria. The number of donkeys included in the research was 96, bred in three regions of Bulgaria -Kardzhali, Stara Zagora and Sofia. Four exterior measurements were taken from each donkey as follow: height at withers, body length, chest circumference and cannon bone circumference. Height at withers and body length were measured with measuring stick the two circumferences were taken with me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 2 publications
0
7
0
Order By: Relevance
“…Height at withers which is reflection of overall body constitution of an individual was also observed to be high in Hassawi donkeys of Egypt & Iraq, Poitevin & Catalan donkeys and Bulgarian donkeys [7] as these donkeys come under the large donkey category. Most of the Indian donkeys match with Balkin, Turkish & Cameroon donkeys with respect to their height at withers [6,8,9].…”
Section: Discussionmentioning
confidence: 87%
“…Height at withers which is reflection of overall body constitution of an individual was also observed to be high in Hassawi donkeys of Egypt & Iraq, Poitevin & Catalan donkeys and Bulgarian donkeys [7] as these donkeys come under the large donkey category. Most of the Indian donkeys match with Balkin, Turkish & Cameroon donkeys with respect to their height at withers [6,8,9].…”
Section: Discussionmentioning
confidence: 87%
“…This limitation arises from the challenges in data availability and the difficulty of monitoring wild animal populations (49). The significant role of donkeys, known to be potential carriers or reservoirs of AHS due to their large population size and wide distribution, cannot be overlooked (50). Excluding donkey data might lead to an underestimation of risk areas or a failure to fully capture the disease’s transmission dynamics.…”
Section: Discussionmentioning
confidence: 99%
“…When it comes to the morphological characteristics of donkeys in Bulgaria, extensive research was done by Vlaeva et al (2016). Studying donkeys in three regions in Bulgaria, the authors found that the average withers height was 119.80 ± 8.09 cm with an interval of variation from 99.0 cm to 148.0 cm.…”
Section: Discussionmentioning
confidence: 99%
“…The exterior traits of domestic donkey in southeastern Serbia were reported by Trailović et al (2011). Extensive research has been done by Vlaeva et al (2016) on the morphological traits of donkeys in Bulgaria. The relationship of head length with ridge height was studied in Romania, Northern Macedonia and Turkey by Urosevic et al (2015).…”
Section: Introductionmentioning
confidence: 99%